Hammer impact test applied for fouling detection in pipelines - Silva,Jaidilson Jó da (2011)
The fouling detection in duct systems is a persistent problem and remains a relevant demand for the chemical, oil, food and pharmaceutical industries. The fouling is a deposition process of heavy organic and other dissolved solid materials in the transported fluids or suspensions onto inner wall surfaces in fluid transport systems. This work presents research results of hammer test for vibration analysis using non-invasive tests to fouling detection in pipelines. Data were taken from the vibration in presence of an inner pipe fouling layer using an accelerometer and a microphone for detection. With the analysis of the obtained results is possible to detect the fouling process, in the monitored pipelines, with and without load conditions, using a microphone and an accelerometer as sensors.